Characterization and evaluation of Indigofera species as potential forage and cover crops for semi-arid and arid ecosystems - Rethman, N.F.G. (University of Pretoria, 2013)
Thesis (PhD (Plant Production: Pasture Science))--University of Pretoria, 2007.